2022
DOI: 10.3390/mi13030386
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Flexibility of an Implantable Neural Microelectrode

Abstract: Neural microelectrode is the important bridge of information exchange between the human body and machines. By recording and transmitting nerve signals with electrodes, people can control the external machines. At the same time, using electrodes to electrically stimulate nerve tissue, people with long-term brain diseases will be safely and reliably treated. Young’s modulus of the traditional rigid electrode probe is not matched well with that of biological tissue, and tissue immune rejection is easy to generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 159 publications
(203 reference statements)
0
13
0
Order By: Relevance
“…One method is to use highly stretchable materials, the other design strategy is geometric design, including wavy banded, 2D serpentine, and 3D spiral structures. 158 Additionally, it has been reported that the fractal and serpentine structure design increases the charge injection ability of the electrode and improves its charge transfer efficiency. 159 This section summarizes the progress in the three types of geometric design.…”
Section: Geometric Engineering Of Stretchable Flexible Nerve Electrodesmentioning
confidence: 99%
“…One method is to use highly stretchable materials, the other design strategy is geometric design, including wavy banded, 2D serpentine, and 3D spiral structures. 158 Additionally, it has been reported that the fractal and serpentine structure design increases the charge injection ability of the electrode and improves its charge transfer efficiency. 159 This section summarizes the progress in the three types of geometric design.…”
Section: Geometric Engineering Of Stretchable Flexible Nerve Electrodesmentioning
confidence: 99%
“…PDMS is a highly flexible synthetic polymer recognized for its elasticity, biocompatibility, biological inertness, gas penetrability, , and low cost . PDMS has been reported to endure years of implantation without degrading or losing flexibility, making it one of the few polymers commonly exploited for medical implant purposes. , However, PDMS is an insulator and thus lacks electrical conductivity. Therefore, despite its attractive mechanical and biocompatible properties, PDMS cannot be used as a standalone material for signal recording purposes.…”
Section: Introductionmentioning
confidence: 99%
“…However, a simultaneous challenge has been to minimize the physical footprint of these components, thereby reducing their in uence on the natural behavior of research subjects [20][21][22] . Tracing the technological evolution from the 1950s, we have witnessed a remarkable transition from metal microwires and bulky transistors to the sophisticated realms of microelectromechanical systems (MEMS) and microelectronics 17,[23][24][25] , signi cantly augmenting recording capacities. Exemplary innovations include the Michigan probe and Utah array [26][27][28] , which utilizes MEMS technology, and state-of-the-art complementary metal oxide semiconductor (CMOS) systems [29][30][31] , such as the Argo system, which supports upwards of 65,536 recording channels 32 .…”
Section: Introductionmentioning
confidence: 99%